Malaysian youth perception towards management of spirituality programs in Malaysia - Maamor, Selamah; Abd Ghani, Abdullah; Abd. Wahab, Norazlina; Aziz, Ahmad Bashir; Ahmad Razimi, Mohd Shahril; Nik Abdullah, Nik Safiah; Elias, Nor Hanim (Academic Research Publishing Group, 2018)
Spirituality Issues among youth should be concerned in order to secure good nation building in future. In relation to this, government as well as private sectors manages to setup various activities in order to develop and improve spirituality among youth. There are three categories of activities: education, training and program offered or managed by government and private sector.However, what is the Malaysian youth perception towards management of spirituality program conducted? Therefore, the objectives of this paper is to measure Malaysian youth perception towards management of spirituality program. The methodologies utilized in this research is quantitative methods to gather primary data through questionnaire. In this study, we employed stratified sampling technique and the respondents are Malaysian youth which age within 15 to 40 years. The data gathered from 4703 respondents analysed by using descriptive analysis, t-test and ANOVA. The findings show that the mean score for effectiveness of management level towards spirituality activities is 7.55 out of 10 points which imply there are room to be improved. There are ample opportunity to improve the management of spirituality activities, especially in terms of selecting professional facilitator or moderator who conduct the spirituality activities.